Application Of 3-Dimensional Modeling In Android-Based Adventure Game Applications - Ari Satrio Wibowo; Agung Kharisma Hidayah; Yuza Reswan; Dandi Sunardi (Penerbit Jurnal Indonesia, 2023)
Role Playing Game (RPG) is a game that has complex story elements and acting that makes a person feel like a character in the game. One of the RPG editing engines is RPG Maker MV, where a 2D RPG can be a standalone program that can be played directly without the help of this program or other programs. Quests are assigned to players by non-player characters (NPCs) that the player cannot control and interact with them through dialogue. In the game mode each player can collect things into an inventory which contains the things needed to solve certain tasks during gameplay. In addition, game objects that represent learning objects have been assigned locations which can be NPCs or other objects. In addition, game objects that represent learning objects have been assigned locations which can be NPCs or other objects. Can apply 3-dimensional modeling to role-playing game applications by placing objects on characters that can walk up, down, left and right. NPC objects can be applied to weapon objects, namely axes, if gold points are collected then the NPC object will appear. It is hoped that this implementation can be a reference not only for 3-dimensional modeling in complex role-playing game applications but also for all circles as the development of Android and IOS-based RPG games.